EVALUATION OF SCOURING AT PILE-SUPPORTED STRUCTURES CROSSING WATERCOURSES ACCORDING TO RELIABILITY AND INHOMOGENEITY INDICATORS OF GROUNDING FOUNDATIONS - A. K. Alibekov (Вестник Дагестанского государственного технического университета: Технические науки, 2018)
Objectives. The aim was to obtain models for predicting local scouring funnel parameters caused by the water flow at the bed by pile foundation supports taking into account the reliability and heterogeneity of the foundation ground.Methods. Mathematical experiment planning methods informed by the theory of similarity and dimensions were used in the work; appropriate processing of the experimental results was carried out.Results. Factors determining the investigated phenomenon were determined. Existing approaches and methods used in already conducted studies were analysed in detail and summarised. For the possibility of setting up the experiments under laboratory conditions and transferring results to field conditions using the methods of the theory of similarity and dimensions, a criterion equation describing the phenomenon of local scouring was obtained. The dimensionality of the multidimensional problem is reduced by taking into account the explicit relationships between the dimensionless factors. The deformability of the foundation grounds is accounted for by the kinematic similarity of the flows. The factorial design of the experiment was justified on the basis of a large number of experimental plans. In this way, the factor space is completely covered, providing a more accurate prediction of the scouring funnel parameters. The intervals and the number of levels of factor variation are determined by analysing the sizes of typical and realistic support designs, taking into account the recommendations and requirements for designing piling pillars; the dimensions of the hydraulic tray for conducting the experiments were also taken into account.  As a result of the processing of experimental data, the required dependencies were obtained for both the absence and input of deposits into the scouring funnel. The adequacy of the obtained models was checked on the basis of independent laboratory experiments and full-scale data on the Brazos and Volga rivers. The heterogeneity of the channel bed grounds is accounted for by the diameter of the pavement particles. To improve the reliability of the local scouring forecast, it is recommended that the obtained dependencies take into account the upper limits of the confidence intervals of the required functions.Conclusion. A technique is proposed for determining the depth and planned parameters of a channel scouring funnel, composed of disjointed grounds near pile-supported structures crossing watercourses with a specified degree of reliability.